Prevalence of and Risk Factors for Nonprescription Antibiotic Use among Individuals Presenting to One Hospital in Saudi Arabia after the 2018 Executive Regulations of Health Practice Law: A Cross-Sectional Study - Ali Mohsen Al-Hazmi; Ahmed Arafa; Haytham Sheerah; Khalid Saeed Alshehri; Khalid Alwalid Alekrish; Khalid Abdulla Aleisa; Abdullah Ali Jammah; Nawaf Abdullah Alamri (MDPI AG, 2021)
Antibiotic resistance is a worldwide public health emergency. Nonprescription antibiotic use is a chief cause of antibiotic resistance. The Saudi Government, as a consequence, imposed in 2018 executive regulations to prevent the distribution of antibiotics without a prescription. Herein, we aimed to investigate the prevalence of and risk factors for nonprescription antibiotic use among individuals presenting to one hospital in Saudi Arabia after enacting these regulations. This cross-sectional study was conducted on people, aged ≥18 years, who presented to the primary healthcare clinics of King Khalid University Hospital in Riyadh during the period between 1/1/2019 and 28/2/2019. Participants were asked to fill out a self-administrated questionnaire assessing their nonprescription antibiotic use during the past year in addition to sociodemographic information. Then, logistic regression analyses were performed to calculate the odds ratios (ORs) and corresponding 95% confidence intervals (CIs) for age, sex, education, and nationality of any nonprescription antibiotic use compared with no use within the past year. Out of 463 participants, 62.9% were females, 67.4% were <40 years, and 93.7% were Saudi citizens. Overall, 30.5% of participants reported nonprescription antibiotic use during the past year (19.7% one to two times and 10.8% more than two times). Male and non-Saudi participants were more likely to report any nonprescription antibiotic use, with HRs (95% CIs) of 1.99 (1.30, 3.04) and 3.81 (1.73, 8.35), respectively. The main reasons behind nonprescription antibiotic use were having previous experience with a health condition (69.2%), inaccessibility of healthcare (26.6%), and recommendation from a relative or a friend (16.1%). A major limitation of this study was that it included individuals attending one hospital. Individuals who seek medical consultation could be dissimilar to those who do not see doctors regarding nonprescription antibiotic use.